Isolation and characterization of lactic acid bacteria from fecal pellets, coelomic fluid, and gastrointestinal tract of Nypa worm (Namalycastis rhodochorde) from West Kalimantan, Indonesia - Ari Hepi Yanti; Tri Rima Setyawati; Rikhsan Kurniatuhadi (Society for Indonesian Biodiversity, 2020)
Abstract. Yanti AH, Setyawati TR, Kurniatuhadi R. 2020. Isolation and characterization of lactic acid bacteria from fecal pellets, coelomic fluid, and gastrointestinal tract of Nypa worm (Namalycastis rhodochorde) from West Kalimantan, Indonesia. Biodiversitas 21: 4726-4731. Lactic acid bacteria isolated from the intestinal tract as probiotic could be beneficial because they could trigger the growth of the host by enhancing digestibility, increasing their immune system, and inhibiting pathogenic bacteria through the enzymatic process or metabolites production. The purposes of this study were to identify and characterize lactic acid bacteria from fecal pellets, coelomic fluid, and gastrointestinal tract of Nypa worm (Namalycastis rhodochorde). Bacterial isolation was carried out by the pour plate method on de Mann Rogosa Sharp Agar (MRSA). Lactic Acid Bacteria (LAB) isolates were purified and then physiologically characterized by some biochemical tests. Cellulolytic activities were carried out by detecting a clear zone formation on CMC-congo Red Agar. There were 20 isolates of lactic acid bacteria from fecal pellets, coelom fluid, and gastrointestinal tract of nypa worm. Ten isolates (50%) had cellulolytic activity on CMC-phenol red agar. Eight isolates were closely related to the genus Lactobacillus, while two isolates were closely related to the genus Bacillus. These cellulolytic bacteria could be developed further as probiotic in Nypa worm feed.